2015
DOI: 10.7727/wimj.2014.103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Normal Ovulation by Sonographic Folliculometry involving Natural Cycles among Women in Ojo, Southwest, Nigeria

Abstract: Sonographic observation of complete disappearance of a dominant follicle and reduction in follicular size of surrogate follicles after follicular rupture appeared to be a reliable predictor of imminent ovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some errors in SMS system where not all participants were sent SMS Fair Domek et al (2016) [ 23 ] Guatemala: caregivers of children presenting for 1st vaccines at 8–14 wks 321 SMS reminders 1 wk prior to 2nd/3rd vaccines Routine care Vaccination coverage: completion of the primary immunisation series Both intervention/control groups had high rates of vaccine completion (visit 2: 95 vs. 90% and visit 3: 84 vs. 81% respectively Pilot study. Service interruptions Fair Eze et al (2015) [ 24 ] Nigeria: caregivers attending health clinics 905 SMS reminders to everyone in intervention group and additional recall SMS to parents who did not attend appointment Routine care Vaccination coverage and vaccination timeliness of receipt of DPT3 prior to 18th week Intervention group DPT3 8.7% higher coverage and received DPT3 1.5 × earlier than controls (OR 1.47, CI 1.1–2.0, p = 0.009) Inconsistent DPT product supply. Randomisation procedures did not account for mobile phone ownership Poor Gibson et al (2017) [ 6 ] Kenya: parents of newborns residing in rural villages 2,018 1) SMS only (3 and 1 day prior to scheduled vaccines at 6, 10 and 14 weeks & 9 months); 2) SMS + low monetary incentive; 3) SMS + higher monetary incentive Routine care Vaccination coverage: Proportion of fully immunised children at 12 months (including BCG).…”
Section: Resultsmentioning
confidence: 99%
“…Some errors in SMS system where not all participants were sent SMS Fair Domek et al (2016) [ 23 ] Guatemala: caregivers of children presenting for 1st vaccines at 8–14 wks 321 SMS reminders 1 wk prior to 2nd/3rd vaccines Routine care Vaccination coverage: completion of the primary immunisation series Both intervention/control groups had high rates of vaccine completion (visit 2: 95 vs. 90% and visit 3: 84 vs. 81% respectively Pilot study. Service interruptions Fair Eze et al (2015) [ 24 ] Nigeria: caregivers attending health clinics 905 SMS reminders to everyone in intervention group and additional recall SMS to parents who did not attend appointment Routine care Vaccination coverage and vaccination timeliness of receipt of DPT3 prior to 18th week Intervention group DPT3 8.7% higher coverage and received DPT3 1.5 × earlier than controls (OR 1.47, CI 1.1–2.0, p = 0.009) Inconsistent DPT product supply. Randomisation procedures did not account for mobile phone ownership Poor Gibson et al (2017) [ 6 ] Kenya: parents of newborns residing in rural villages 2,018 1) SMS only (3 and 1 day prior to scheduled vaccines at 6, 10 and 14 weeks & 9 months); 2) SMS + low monetary incentive; 3) SMS + higher monetary incentive Routine care Vaccination coverage: Proportion of fully immunised children at 12 months (including BCG).…”
Section: Resultsmentioning
confidence: 99%
“… 28-33 Text messaging appears to be the most popular, but its applicability is limited in many countries by cost considerations, poor network coverage, and low literacy levels, as also shown in Nigeria. 33 , 34 Additionally, transmission delays due to power cuts, 31 and messaging (data entry) errors were reported as constraints. 35 In our study only about a third (153/427) of mothers/caregivers had basic Western education and only 35% (154/435) owned a personal phone.…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, a plan for the modernization of agriculture was introduced to address the needs of the majority engaged in agriculture [12]. Despite the slow economic recovery in Northern and Eastern Uganda, where insecurity remains a hurdle to poverty reduction, macroeconomic policies at the national level contributed significantly to reducing poverty from 35% in the 1990s to 19 Survey. This comprehensive study [22] revealed that household poverty in the country stood at 21.4%, with rural areas experiencing a higher incidence at 25%, compared to 9.6% in urban areas.…”
Section: Economic Interventionsmentioning
confidence: 99%